2015
DOI: 10.3390/ijerph13010061
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Assessment of Environmental Health Impacts for Policy Support: The Example of Road Transport in New Zealand

Abstract: An integrated environmental health impact assessment of road transport in New Zealand was carried out, using a rapid assessment. The disease and injury burden was assessed from traffic-related accidents, air pollution, noise and physical (in)activity, and impacts attributed back to modal source. In total, road transport was found to be responsible for 650 deaths in 2012 (2.1% of annual mortality): 308 from traffic accidents, 283 as a result of air pollution, and 59 from noise. Together with morbidity, these re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 50 publications
0
18
0
1
Order By: Relevance
“…Hanninen et al 2014 estimated in an environmental BOD assessment the DALYs attributable to the environmental stressors of benzene, dioxins, second-hand smoke, formaldehyde, lead, traffic noise, ozone, particulate matter (PM2.5), and radon, in six European countries and found that about 3-7% of the annual BOD in the six countries is associated with the considered environmental stressors. A study for sparsely populated New Zealand, estimated 25,000 DALYs attributable to traffic incidents, air pollution and noise (Briggs et al, 2016), while a study for the region of Flanders, Belgium found that 11% of the population were severely annoyed and 7% were highly sleep disturbed from environmental noise (Stassen et al, 2008). Finally, Ling-Yun and Lu-Yi 2016 estimated the effect of reducing the kilometres travelled by Chinese residents by 5% and 10% via increasing cycling, and suggested this would lead to around 1.56% and 3.11% decrease in annual average concentrations of SO2, and 1.40% and 2.80%, 3.09% and 6.18%, 2.93% and 5.86% decrease in NO2, PM2.5 and PM10, respectively.…”
Section: Quantitative Health Impact Assessmentmentioning
confidence: 99%
“…Hanninen et al 2014 estimated in an environmental BOD assessment the DALYs attributable to the environmental stressors of benzene, dioxins, second-hand smoke, formaldehyde, lead, traffic noise, ozone, particulate matter (PM2.5), and radon, in six European countries and found that about 3-7% of the annual BOD in the six countries is associated with the considered environmental stressors. A study for sparsely populated New Zealand, estimated 25,000 DALYs attributable to traffic incidents, air pollution and noise (Briggs et al, 2016), while a study for the region of Flanders, Belgium found that 11% of the population were severely annoyed and 7% were highly sleep disturbed from environmental noise (Stassen et al, 2008). Finally, Ling-Yun and Lu-Yi 2016 estimated the effect of reducing the kilometres travelled by Chinese residents by 5% and 10% via increasing cycling, and suggested this would lead to around 1.56% and 3.11% decrease in annual average concentrations of SO2, and 1.40% and 2.80%, 3.09% and 6.18%, 2.93% and 5.86% decrease in NO2, PM2.5 and PM10, respectively.…”
Section: Quantitative Health Impact Assessmentmentioning
confidence: 99%
“…Researchers have assessed the effects of traffic pollution controls around the world from many perspectives, such as emission mitigation, air quality improvement, and health damages reduction (17)(18)(19)(20). The majority of studies of traffic pollution controls in China have assessed benefits solely in terms of their impacts on emissions at either the national (16,21) or local level (22,23).…”
mentioning
confidence: 99%
“…A study for Warsaw, one of the most congested cities in Europe, estimated annually 58000 DALYs attributable to noise, air pollution and traffic injuries (with noise contributing the largest), and a health gain of 17000 DALYs avoided due to transport-related PA (Tainio, 2015). A recent study for sparsely populated New Zealand, found 25000 DALYs attributable to traffic incidents, air pollution and noise (Briggs et al, 2016). Another recent study estimated 400 to 800 DALYs per 100000 persons avoided due to changes in PA, air pollution and traffic incidents in Boston, Copenhagen, Delhi, London, Melbourne and São Paulo under a compact city scenario (Stevenson et al, 2016).…”
Section: Discussionmentioning
confidence: 99%